Monoclonal antibodies carried in drug delivery nanosystems as a strategy for cancer treatment - Silvestre, Amanda Letícia Polli [UNESP]; Oshiro-Júnior, João Augusto; Garcia, Camila [UNESP]; Turco, Bruna Ortolani [UNESP]; Leite, Joandra Maísa Da Silva; Damasceno, Bolivar Ponciano Goulart De Lima; Soares, Jonas Corsino Maduro [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2021)
Monoclonal antibodies carried in nanosystems have been extensively studied and reported as a promising tool for the treatment of various types of cancers. Monoclonal antibodies have great advantages for the treatment of cancer because their protein structure can bind to the target tissue; however, it has some challenges such as denaturation following heat exposure and extreme values of pH, temperature and solvents, the ability to undergo hydrolysis, oxidation and deamination and the formation of non-native aggregates, which compromise drug stability to a large extent. In addition to these characteristics, they suffer rapid elimination when in the blood, which results in a short half-life and the production of neutralizing antibodies, rendering the doses ineffective. These challenges are overcome with encapsulation in nanosystems (liposomes, polymer nanoparticles, cyclodextrins, solid lipid nanoparticles, nanostructured lipid carriers, dendrimers and micelles) due to the characteristics of improving solubility, permeability, and selectivity only with tumor tissue; with that, there is a decrease in side effects beyond controlled release, which is critical to improving the therapeutic efficacy of cancer treatment. The article was divided into different types of nanosystems, with a description of their definitions and applications in various types of cancers. Therefore, this review summarizes the use of monoclonal antibodies encapsulated in nanosystems and the description of clinical studies with biosimilars. Biosimilars are defined as products that are similar to monoclonal antibodies which are produced when the patent for the monoclonal antibodies expires.
Keywords: Antibodies; Biopharmaceuticals; Biosimilars; Cancer treatment; Drug delivery nanosystems; New therapy